Análise do consumo e constituintes químicos de vinhos produzidos na Quarta Colônia de Imigração Italiana do Rio Grande do Sul e sua relação com as frações lipídicas sangüíneas - Blasi, Tereza Cristina (2004)
The Quarta Colônia of Italian immigration and centenary existence, which is located in the central region of the state, produces homemade wine from non-vining varieties such as Bordeaux, Isabel and Concord, among others. In this way, the aim of this work was to analyze the chemical characteristics of these wines, as well as, their relation with the lipidic profile of this population which consumes wine. The wines, from seven towns, were analyzed with five samples each one, with respect to pH, by means of a peagameter reading; total and volatile acidity by titulometry with sodium hydroxide; total and free sulfite by titulometry with iodine; reductive sugar by Lane & Eynon method; alcohol by distillation in Gibertini; total and free antocianas by the method described by Di Stefano; and polyphenol by colorimetric method described by Singleton. All results were among current legislation, with the exception of alcohol level, which has presented a lower value of 9,89ºGL, considering the law which ranges from 10 to 13ºGL.. In relation to lab exams, they have presented positive values in relation to triglycerides and HDL-c in which, most of the population have presented suitable results according to values of reference described on III Directives on dislipidemias and arteriosclerosis. Total cholesterol and LDL-c have shown results above reference values, which is consider a risk factor for the population. Information on chemical analysis of wines and lab exams were handed in to wine producers. It is necessary a periodical chemical evaluation of these wines in order to create a pattern of quality and storage, bringing on to light the importance of a balanced nourishment for the population, which can have a great influence on the blood samples parameters and wine ingestion.